2015
DOI: 10.14503/thij-13-3731
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of a Cavopulmonary Tumor Embolus with the Use of Transesophageal Echocardiography

Abstract: P ulmonary tumor embolization from renal cell carcinoma (RCC) is associated with severe cardiopulmonary morbidity and high perioperative mortality rates. In one study, 1 the direct extension of RCC into the inferior vena cava (IVC) was observed in 22 of 295 patients (7%). Massive pulmonary embolism (PE) can occur during surgical treatment for RCC, especially when the tumor extends into the IVC.2-6 Advantages of using transesophageal echocardiography (TEE) during RCC excision include evaluating the cephalic ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…TEE is an option, apart from the perioperative period or interventional procedures, in visualization of thrombus or vegetation, in etiologic differentiation of syncope, or where TTE is inadequate for diagnosis. In the case of syncope or transient ischemic attack, the anatomically opened foramen ovale (PFO) might need to be closed (17,18). During TEE evaluation by colored Doppler or agitated serum injection, shunting of blood through the PFO can be definitely shown (14).…”
Section: Discussionmentioning
confidence: 99%
“…TEE is an option, apart from the perioperative period or interventional procedures, in visualization of thrombus or vegetation, in etiologic differentiation of syncope, or where TTE is inadequate for diagnosis. In the case of syncope or transient ischemic attack, the anatomically opened foramen ovale (PFO) might need to be closed (17,18). During TEE evaluation by colored Doppler or agitated serum injection, shunting of blood through the PFO can be definitely shown (14).…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of right ventricular systolic and diastolic dysfunction, 22-30 pulmonary hypertension, 31-33 assessment for IVC stenosis in liver transplantation, heart transplantation, ECMO, and artificial heart, 9,24,[34][35][36][37][38][39][40][41][42] ruling-out abdominal IVC tumor [43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] or thrombus 45,48,56,[58][59][60][61][62] as a cause of pulmonary embolism and right-to-left shunting through a PFO in hypoxic patients with right heart dilation, 45,48,56,[58][59][60][61] and abdominal compartment syndrome 24,34,63 ; intraoperative monitoring during renal cell carcinoma surgery involving the inferior vena cava 43,45,46,…”
Section: Abdominal Vasculaturementioning
confidence: 99%
“…Abdominal Transgastric Ultrasonography level of the left hepatic lobe, between the stomach and the heart (Supplemental Digital Contents 12 and 15, Figure 5E, Video View 3, http://links.lww.com/AA/ D479, http://links.lww.com/AA/D482). Several authors have also reported on the role of TGAUS in managing patients with renal tumor extending to the IVC, 43,[45][46][47][48][49][58][59][60][61]64 which is discussed in the following section. The hepatic venous velocity patterns can give insight into hepatic perfusion as well as right heart dynamics.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Studies show no consistent difference between the two modalities [41][42][43] Early identification of children at risk for tube feedings and subsequent early feeding tube placement will likely decrease hospital length of stay. 44 Risk-adjusted comparison of temporary versus surgical tubes is necessary to help determine which type of feeding tube, if any, is superior with regard to safety and/or improved outcomes after neonatal cardiac surgery.…”
Section: Feeding Tubesmentioning
confidence: 99%